2021
DOI: 10.2147/jaa.s299796
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Olfactory Function and Asthma in Adults

Abstract: Purpose: Chronic rhinosinusitis (CRS) and allergic rhinitis (AR) are common asthmaassociated upper airway diseases. Olfactory dysfunction, a common symptom among these patients, is an increasingly recognized condition that is associated with a reduced quality of life and major health outcomes. However, there are few studies on the association between olfactory function and asthma. We investigated the relationship between asthma and olfactory function. Patients and Methods: A total of 146 patients with asthma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Another possible explanation could be a self-selection away from areas with polluted areas among individuals with asthma. Since asthma has been shown to be associated with worse olfactory function (Rhyou et al 2021) this could potentially lead to bias towards the null in our study. A limitation in this study is that we do not have access to data regarding asthma for our participants; thus, we could not investigate the role of it in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Another possible explanation could be a self-selection away from areas with polluted areas among individuals with asthma. Since asthma has been shown to be associated with worse olfactory function (Rhyou et al 2021) this could potentially lead to bias towards the null in our study. A limitation in this study is that we do not have access to data regarding asthma for our participants; thus, we could not investigate the role of it in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Rhyou et al. conducted a clinical investigation on olfactory dysfunction in patients with asthma, which indicated that the incidence of olfactory disturbance in patients with CRS or AR associated with asthma was 56.5%, whereas the incidence of olfactory disturbance in patients with asthma alone was only 15.8% ( 10 ). Lacking direct research, the pathogenesis of asthma linked to olfactory dysfunction warrants further investigation.…”
Section: Asthma-associated Brain Response Phenotypes and Mechanismsmentioning
confidence: 99%
“…Asthma is characterized by non-specific respiratory symptoms such as wheezing, shortness of breath, chest tightness, and episodic cough as the main clinical manifestations, which frequently occur at night and early in the morning, and its main pathogenesis is chronic immune-inflammatory response, airway hyperreactivity, reversible airflow limitation, and airway remodeling ( 6 , 7 ). Patients with asthma are often accompanied by neurological symptoms such as cognitive dysfunction, depression, anxiety, dysosmia, and sleep disorders, implying a brain response to asthma, which affects their quality of life, increases their economic burden, reduces the treatment sensitivity of asthma, increases the risk of asthma exacerbations, and forms a vicious cycle ( 8 10 ). Based on our previous summary of brain response in allergic rhinitis (AR) ( 11 ), a “lung–brain” crosstalk in asthma can be observed on the basis of neuro-immune mechanisms, that is, inflammatory factors generated during chronic inflammation in asthma can be transmitted upwards to the central nervous system, thereby stimulating associated brain regions to elicit one or more brain responses, transmitting response commands to peripheral nerves, activating such commands to release mediators such as neuropeptides and neurogenic trophic factors, worsening asthma symptoms through actions such as tracheal smooth muscle contraction, promoting the re-entry of immune inflammatory factors produced in the periphery to the brain, and exacerbating neurological symptoms caused by brain response ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%